FAKTOR BERHUBUNGAN DENGAN LAMA RAWAT PASIEN TERKONFIRMASI COVID-19 DI WILAYAH PUSKESMAS BREBES - Lely Wahyuniar; Dwi Nastiti Iswarawanti; Dewi Laelatul Badriah; Sutaip Sutaip (Journal of Midwifery and Health Administration Research, 2023)
Background: The average length of stay for COVID-19 patients in Central Java is 17 days, Brebes regency and in the working area of the Brebes Health center is 14 days. COVID-19 patients are at risk of increasing length of stay due to various factors and the increased length of stay can increase the burden of health services. The purpose of this study was to determine the factors that influence the length of stay of COVID-19 patients. Methods: This type of research was analytic descriptive with a correlational design. The population of this study was patients with confirmed COVID-19 in the working area of ​​the Brebes Community Health Center which was 642 patients, with a total sample of 247 determined by the Slovin formula. The used analyses were univariate, bivariate analysis with Chi-square, andMultivariate analysis with multiple logistic regression. Results: Chi-Square test showed age variable with p-value 0.002, gender p-value 0.995, work p value 0.007, clinical symptoms p-value 0.001, comorbid p-value 0.022, administration day admission p-value 0.603, administration discharge status p-value 0.001. Mutivariate resulth obtained Odds Ratio (OR) on clinical symptoms OR 16,995, discharge status OR 12.264, comorbities OR 6.855. Conclusion: There is a relationship between the variables of age, clinical symptoms, comorbidities, adminstration and lengh of stay of patients confirmed with COVID-19 in the working area of the Brebes Publich Center. Clinical symtoms are determinants of the length of stay for COVID. It is recommented that Health Center Brebes and Hospital can improve the quality of COVID care services.